RUSSIAN GEOLOGY AND THE PLATE TECTONICS REVOLUTION - Khain V.E.; Ryabukhin A.G. (My University, 2002)
The suggestion of the concept of 'scientific revolution' by Thomas Kuhn in 1962 was, in itself, a significant event in the history of science, and 'crucial' episodes or 'paradigm shifts' have come to be of special interest in the history of geology (as in other sciences). The appearance of a new paradigm is commonly associated with attempts by the most talented and well-established practitioners to consolidate or sustain the position of the previously prevailing paradigm. For almost 40 years, global theories in geology have been developing under the influence of mobilist ideas. It is no secret that in Russia the mobilist school initially met with serious opposition, and that even up to the present it has had numerous opponents. However, Western, and especially popular, scientific literature usually exaggerates the intensity of the situation and underestimates the contribution of Russian geologists and geophysicists to the development of mobilism and plate tectonics. The present paper describes some of the debates in Russia concerning mobilist doctrines, the work done in that country in the last three decades of the twentieth century from a mobilist perspective, and various theories that had currency in Russia at the end of that century.